PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY DIVARIASIKAN DENGAN MIND MAPPING TERHADAP LITERASI SAINS DAN HASIL BELAJAR SISWA KELAS VII SMPN 17 PEKANBARU - Tamara, Annisa Gusri; Yustina, Yustina; Fauziah, Yuslim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstarct: Has do reasearch to describe effect use Guided Inquiry Learning varied with Mind Mapping for sciencetific literacy and learning result of the 7th grade students of Junior High School 17 Pekanbaru. Form of research is a pre-experiment design research with pretest-posttest one group design. This research was conducted on August up to October 2018. The sample selected with purposive sampling technique, VII.1 class with 37 students. The results showed that category improvement of student’s sciencetific literacy and learning result in experiment class after use Guided Inquiry Learning varied with Mind Mapping are respectively (N-gain=0,61) and (N-gain=0,59) was medium category. According to study results, it could be concluded that: 1) use Guided Inquiry Learning varied with Mind Mapping are effected for students sciencetific literacy 2) use Guided Inquiry Learning varied with Mind Mapping are effected for learning result of the 7th grade students of Junior High School 17 Pekanbaru.Key Words: Guided Inquiry Learning, Mind Mapping, Sciencetific Literacy